Development of nutrient-Rich purple Sweet potato and moringa-based biscuits as an alternative snack for toddlers at risk of stunting. - Rahman, Nurdin; Sakung, Jamaluddin M; Ariani, Ariani; Rakhman, Aulia (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: This study aims to address the nutritional needs of young children while utilizing local food resources in Central Sulawesi, Indonesia. Methods: This study employs a descriptive method based on laboratory tests for nutrient content analysis and acceptability. The research design utilizes a Completely Randomized Design (CRD) with 5 treatments of varying substitutions of purple sweet potato flour and moringa flour. The analysis of carbohydrate, fat, protein, ash, moisture, and fiber content is conducted by descriptively comparing each formula. Results: Carbohydrates, namely formula F5 has the highest carbohydrate content of 52.2%, Fat, namely formula F1 has the highest fat content of 35.7%, Protein, namely formula F1 also has the highest protein content of 15.38%. Water Content, namely formula F1 has the highest water content of 2.55%, Ash Content, namely formula F1 also has the highest ash content of 4.84%, Fiber Content, namely formula F3 has the highest fiber content of 5.12%. F1 formula biscuits have relatively strong antioxidant power with an IC50 of 94.655 ppm compared to other formulas. Sensory analysis revealed significant differences in the perception of quality and preference for color, aroma, and taste among the five formulas. The highly significant differences in color and taste preferences indicate that the composition of each formula has a substantial influence on the product's sensory characteristics. Conclusion: Purple sweet potato and Moringa leaf-based biscuits demonstrate potential as a nutritious snack for children experiencing stunting and wasting due to their favorable nutritional content and relatively high acceptance rate. However, further research is necessary to determine the optimal formulation that maximizes nutritional value while maintaining sensory qualities acceptable to children